OPTIMALISASI POTENSI BUAH PALA DI DESA BOBO KECAMATAN JAILOLO KABUPATEN HALMAHERA BARAT - Nihi, Sriyanti; Torano, Abidil Haq; Anggraini, Hana Sagita; Bahrudin, Riskiani; Rawung, Deviana Andrini; Parenrengi, Ferdiansya Mahardika (Al-Mulk: Jurnal Pengabdian Masyarakat, 2023)
Nutmeg is a native plant originating from Indonesia, especially the North Maluku region. One area that has quite a lot of nutmeg trees is Bobo Village, Jailolo District, West Halmahera. This research aims to describe the use of nutmeg flesh to be processed into nutmeg jam. This research was carried out from August 21 2023 until the report was prepared in September 2023. The data used was through interviews with resource persons, namely Mama Ida and PKK mothers as well as through holding training in making nutmeg jam. This analysis uses the ABCD (Asset Base Community Development) method, which is a method that uses 5 key steps to carry out the service process, including Discovery, Dream, Design, Define, Destiny (do) and reflection. From the results of this research, it can be seen that the implementation of the nutmeg jam making training can be realized well, starting from the request to the resource person to be a speaker, then the collaboration between the Bobo village government and the IAIN Ternate Religious Moderation Collaboration KKN KKN students in holding the nutmeg jam making training.Keywords: Nutmeg; Nutmeg Jam; Training on Making Nutmeg Jam.